A history of marxist psychology
1 online resource (vi, 212 pages)
Keywords: "An illuminating and original collection of essays on 20th Century Russian psychology, offering unparalleled coverage of the scholarship of Vygotsky and his peers. Yasnitsky et al challenges our assumptions about the history of Soviet science and the nature of Soviet Marxism and its influence on psychological thinking. He significantly broadens the discussion around Vygotsky's life and work and its historical context, applying theories of other notable thinkers such as Alexander Luria and the much-neglected philosopher/psychologist Sergei Rubinstein, alongside key movements in history, such as the pedology and psychohygiene. A diverse range of researchers from countries such as, Argentina, Brazil, Canada, France, Russian Federation, Switzerland, Ukraine, and UK, give this book a truly global outlook. This is an important and insightful text for undergraduate and postgraduate students and scholars interested in the history of psychology and science, social and cultural history of Russia and Eastern Europe, Marxism, and Soviet politics"--